Persepsi Petani terhadap Program Upaya Khusus Peningkatan Produksi Padi, Jagung, dan Kedelai (Kasus Teknologi SRI di Subak Lungatad, Desa Peguyangan Kangin, Kecamatan Denpasar Utara, Kota Denpasar) - I GEDE NGURAH SWARNA DWIJA INDRATANAYA; I DEWA PUTU OKA SUARDI; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Perception of Farmers on Special Efforts to Increase Rice, Corn and SoybeanProduction (The Case of SRI Technology in Subak Lungatad,Peguyangan Kangin Village, Denpasar City)The need for food is one of the main aspects for the survival of society. Special Foodfor food self-sufficiency 2015-2017 is the effort of the Ministry of Agriculture tosucceed in self-sufficiency in rice, corn, soybeans in 2017. One of the hopes as the bestsolution for agriculture in Indonesia in increasing production is through a method offarming patterns with the System of Rice Intensification (SRI). The purpose of thisstudy was to find out the perception of farmers on the Upsus Pajale program, especiallySRI technology in Subak Lungatad, Peguyangan Kangin Village, North DenpasarDistrict. The number of samples was 30 farmers. The data were gathered throughquestionnaires using quantitative and qualitative data types. The data that had beenprocessed were further analyzed using qualitative descriptive analysis method.Research results show that the farmers' perceptions of SRI technology: (1) innovationwas in good category with a score of 3.96, (2) social aspects were in good category witha score of 3.61, (3) economic aspects were in good category with a score of 4.09. And(4) the technical/ environmental aspects were also in the good category with a score of3.48.Based on the results of the research and conclusions obtained, the suggestion that can bemade to the government is that they should provide more input on the SRI plantingsystem, both through technical guidance, field practice (making demonstration plots)and mentoring during each planting season, so that the results achieved could berailored to the expectations of all parties. It is also recommended that they should paymore attention to the rice sales system which is currently being sold using a slashsystem, with the calculation using the area (acre), thus making it difficult for farmers toobtain optimal benefits.